(untitled) (Estudios de Historia de España, 2021)
Even though the Florentins were the Toscan merchants with most presence in Valencia, there were also Pisans, especially during the XV century. Some of them, like some members of the Vernegallo (Vernegal) family, settled definitively in Valencia, from where they directed their various business: commerce, bills of exchange, loans, leases, properties and lands, etc. After settling in the city the Vernegal became citizens of the same, leaving behind their condition of foreigners and integrating in the urban social body, at the same time that their monetary fortune let them become part of the economic elite.